M1-like Macrophage Polarization Promotes Orthodontic Tooth Movement. (September 2015) - He, D.; Kou, X.; Yang, R.; Liu, D.; Wang, X.; Luo, Q.; Song, Y.; Liu, F.; Yan, Y.; Gan, Y.; Zhou, Y.
Macrophages play a crucial role in inflammatory-mediated bone loss. Orthodontic tooth movement (OTM) is associated with inflammatory bone remodeling. However, whether and how macrophages contribute to mechanical force–induced OTM remains unknown. In this study, we hypothesized that polarization of M1-like macrophages may contribute to the OTM. Orthodontic nickel-titanium springs were applied to the upper first molars of rats or mice to induce OTM. The distance of OTM gradually increased after mechanical force was applied to the rats for 5 and 10 d. M1-like macrophage polarization and expression of M1 cytokine tumor necrosis factor (TNF)-α also increased after force application. More importantly, monocyte/macrophage depletion in mice by injection of clodronate liposomes decreased the distance of OTM and the number of tartrate-resistant acid phosphatase (TRAP)–positive osteoclasts and CD68 + macrophages, accompanied by reduced expressions of M1 markers TNF-α and inducible nitric oxide synthase (iNOS), whereas systemic transfusion of M1 macrophages in mice increased them. Further experiments showed that injection of recombinant TNF-α increased the distance of OTM and the number of TRAP-positive osteoclasts and CD68 + macrophages, as well as upregulated the expression of TNF-α and iNOS. Blockage of TNF-α by etanercept injection reduced the distance of OTM and the number of TRAP-positive osteoclasts and CD68 + macrophages, as well as decreased the levels of TNF-α and iNOS. These data suggest that M1-like macrophage polarization promotes alveolar bone resorption and consequent OTM after mechanical force application.